ANALISIS KEMAMPUAN NUMERASI PADA SISWA KELAS IV SEKOLAH DASAR - Nur Chasanah; Sumarno; Ida Dwijayanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Mathematics is one of the subjects in the Independent Curriculum at elementary school level. One part of Mathematics is numeration. Currently, numeracy is one of the achievements measured in the Minimum Competency Assessment (AKM). AKM at the elementary school level is implemented for fifth grade students, so there needs to be preparation in previous grades to deal with it. Numeracy is the ability to think using concepts, procedures, facts and mathematical tools to solve everyday problems in various types of relevant contexts. Numeracy skills can help students study other fields of science, help students think and digest information in written or quantitative form. However, based on research, many students experience difficulties in counting and teachers also encounter problems in teaching counting. So this research aims to determine: (1) the numeracy abilities of fourth grade elementary school students; (2) mathematics learning difficulties in terms of numeracy abilities in fourth grade elementary school students; and (3) teachers' efforts to overcome obstacles encountered when teaching numeracy. The research method used is qualitative descriptive research. The research was carried out in semester 2 of the 2023/2024 academic year. This research used subjects selected by purposive sampling using the technique of (1) interviewing 15 teachers and (2) giving numeracy assessment sheets to 30 students from 3 different elementary schools, namely SDN Sidomulyo, SDN Sendangmulyo, and SDN 1 Gunem. Based on the research results, 1 student got a score of ≤40, 22 students got a score of 41 – 70, and 7 students got a score of ≥71. Meanwhile, from interviews with teachers, all teachers stated that they had overcome obstacles when teaching numeracy.